Investment and Sustainable Real Estate in the Czech Republic - Safari, Marc; Semenenko, Vadim; Čajka, Radek, 1983-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
This thesis explores the impact of climate change on the Czech Republic's commercial real estate market, focusing on investment decision-making. Through a detailed literature review and qualitative research, including interviews with industry professionals, the study evaluates the risks and opportunities climate change presents to real estate investments. The findings emphasize the increasing importance of environmental standards and ESG (Environmental, Social, and Governance) compliance in the Czech real estate sector. With regulatory pressures and global sustainability trends rising, the research highlights the need for strategic adaptation to maintain competitiveness and avoid stranded assets. The challenges of retrofitting older buildings and the slow adoption of ESG tools are addressed, illustrating the complexities of transitioning to greener real estate practices. This thesis offers valuable insights for real estate investors, emphasizing that integrating climate-aware practices is not only a trend but a necessity for long-term success in the evolving market landscape.
Vedoucí práce: Vadim Semenenko
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses